Genome-wide association analyses identifies a susceptibility locus for tuberculosis on chromosome 18q11.2. - Thye, T; Vannberg, F; Wong, S; Owusu-Dabo, E; Osei, I; Gyapong, J; Sirugo, G; Sisay-Joof, F; Enimil, A; Chinbuah, M; Floyd, S; Warndorff, D; et al. (2010)
We combined two tuberculosis genome-wide association studies from Ghana and The Gambia with subsequent replication in a combined 11,425 individuals. rs4331426, located in a gene-poor region on chromosome 18q11.2, was associated with disease (combined P = 6.8 x 10(-9), odds ratio = 1.19, 95% CI = 1.13-1.27). Our study demonstrates that genome-wide association studies can identify new susceptibility loci for infectious diseases, even in African populations, in which levels of linkage disequilibrium are particularly low.